Broadband pin diode switching and phase shifting - Hirson, Desmond (Department of Electrical Engineering, 2016)
Investigation into the limitations on the bandwidth of PIN diode switches in their different configurations is performed. The Single Pole Double Throw switch constructed with shunt mounted PIN diodes is shown to be bandlimited due to the line lengths involved in the operation. Series mounted diode switches have a wider bandwidth but the diodes cannot perform as power devices due to their physical construction. Radiation due to discontinuities were found to degrade the isolation but this was overcome by an evanescent waveguide structure. The software program TOUCHSTONE (TM)/RF by EEsof is used extensively as a basic development tool. The characterisation of the PIN diodes which was used by the software, was carried out. A bias network had to be developed to allow for the biasing of the diodes before any test boards could be fabricated. A literature survey was done on the different types of phase shifters available. A circuit which enables shifts in 45 degree increments was developed. The system consists of Reflection Phase Shifters which are made up of Quadrature Couplers that have different terminations switched in on two of their ports, a Wilkinson power splitter and a power combiner in the form of a 3 dB Quadrature Coupler. It was found that this configuration works well in theory but is too demanding on the practical components to allow for low phase shift errors to occur.